Bcy1, the regulatory subunit of cAMP-dependent protein kinase in yeast, is differentially modified in response to the physiological status of the cell - Werner-Washburne, M. (University of New Mexico, Albuquerque, NM); Brown, D; Braun, E (The Journal of biological chemistry, 1991)
The regulatory subunit of cAMP-dependent protein kinase in yeast, encoded by the BCY1 gene, is known to be required under certain conditions such as growth on nonfermentable carbon sources and entry into stationary phase. We have identified novel isoforms of Bcy1 in cells under these conditions. The isoforms are distinguishable by their migration on one-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and 2-dimensional nonequilibrium pH gradient gel electrophoresis. The isoforms observed by one-dimensional SDS-PAGE bind cAMP, as determined by [32P]8-azido-cAMP labeling (diagnostic of Bcy1 protein). Proteins isolated from cells grown to stationary phase in rich medium exhibit five antibody-reactive bands, by one-dimensional SDS-PAGE immunoblot analysis, with apparent molecular masses of 50, 52, 55, 59 and 61 kDa. Total Bcy1 protein increases at least 8-fold between exponential and stationary phase. Analysis of proteins from a variety of yeast mutants indicated that 1) many of the observed modifications of Bcy1 are dependent upon the presence of the Ser-145 phosphorylation site; 2) the appearance of the 59- and 61-kDa bands is dependent upon the presence of Yak1 kinase; and 3) Bcy1 protein is modified even in the absence of cAMP-dependent protein kinase catalytic subunits. Cells carrying the bcy1(ala145) allele exhibit non-wild type growth, indicating that these modifications may be functionally significant